Makna Filosofis Tradisi Syawalan (Penelitian Pada Tradisi Syawalan di Makam Gunung Jati Cirebon) - Afghoni, Afghoni (LP2M IAIN Palangka Raya, 2017)
Syawalan is an annual communal tradition in Gunung Jatiâs funeral, Cirebon. There are interesting simbolics behavior to research. These symbolic behavior are very meaningful to Cirebon community. The research describes philosophic meaning of an annual tradition of Cirebon community and Cirebon Keraton. It uses descriptive and phenomenological research method. Sultan and the societies make a pilgrimage to the Sunan Gunung Jatiâs grave while tahlilan,Â Â the societies also bring rice or money, Sultan gives offerings to them, saweran and take a bath at seven sacred well. Philosophical meaning of the tradition is ngalap berkah. Ngalap berkah is covering the meaning of benefincence in spiritual, social, economy, and politic.Â